A systematic approach for the thermodynamic modelling of CO2-amine absorption process using molecular-based models. (15th December 2018) - Pereira, Luís M.C.; Vega, Lourdes F.
Highlights: Accurate molecular models are used to describe CO2 absorption in aqueous amines. Only two model parameters are required to represent the absorption process. Model tested for five amines over a broad range of thermodynamic conditions. The model accurately predicts the absorption of CO2 in amine blends. Cyclic capacity and energy requirements are estimated for selected amine systems. Abstract: The development of new amine systems for CO2 capture is a topic of high interest because of the limitations current aqueous amine systems have for capturing CO2 at large scale. Having a robust and systematic approach for describing the absorption of CO2 would help accelerating the discovery of high performance amine solvents. In this contribution, a molecular-based equation of state is applied to describe the absorption of CO2 in aqueous solutions of single and blended amines at conditions of relevance for post-combustion CO2 capture. A scheme of implicit reactions is used to describe the formation of carbamate and/or bicarbonate products resulting from the chemical reactions between CO2 and five amines of practical industrial interest. This procedure eliminates the need to specify the detailed equilibrium reactions and significantly reduces the number of parameters required to represent the absorption process. A maximum of two adjustable model parameters (one of which with a linear temperature dependence), optimised for a fixed amine concentration, suffices to represent the absorption of CO2 in aqueous solutions of single amines over a broad range of temperatures (298–413 K) and partial pressures of CO2 (0.1–1000 kPa). The extrapolation capabilities of the model are tested by predicting the absorption of CO2 in aqueous solutions of single amines for different amines concentrations (∼8.5–35 wt%), with modelling results showing good quantitative agreement with solubility, speciation and enthalpy of absorption data available in literature. Furthermore, without introducing any new model parameter, the absorption of CO2 in various amine blends is satisfactorily predicted by considering competing interactions for the reactive sites in the model of CO2 . The developed models are then used to assess the CO2 capture performance of selected amine systems in terms of two key process parameters: solvent cyclic capacity and regeneration energy. Results for systems with the same total amine mass concentration show that the highest molar cyclic capacities are obtained for 30 wt% piperazine (0.45 mol CO 2 .mol Amine - 1 ), whereas the greatest energy savings for solvent regeneration are estimated for 30 wt% methyldiethanolamine (2.3 GJ .tCO 2 - 1 ). Moreover, two piperazine–promoted blends showed the potential for reducing up to ∼26% the energy consumption for solvent regeneration and separating up to ∼41% more CO2 in a molar basis when compared to the benchmark 30 wt% monoethanolamine. Altogether, these results demonstrate the feasibility of the developed approach as a reliable platform for the screening of amine solvents as function of key process parameters, and as a valuable tool for process modelling.